2016
DOI: 10.1080/09712119.2016.1258363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different carbohydrate sources on activity of rumen microbial enzymes and nitrogen retention in sheep fed diet containing recycled poultry bedding

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Effects of different carbohydrate sources on activity of rumen microbial enzymes and nitrogen retention in sheep fed diet containing recycled poultry bedding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…According to a study by Raghuvansi et al (2007) , the increase in the production of fibrolytic enzymes could be attributed to the higher numbers of fibrolytic bacteria. Our results indicated that group S1 showed higher enzymes activities (cellulase and xylanase), and a higher bacterial population followed by S3 ( Table 4 ); this finding could be attributed to the presence of rapidly degradable carbohydrates and degradable nitrogen in S1 groups that stimulated bacterial growth ( Raghuvansi et al, 2007 ; Azizi-Shotorkhoft et al, 2018 ). Moreover, higher cellulase production and bacterial population in S3 compared to S2 could be explained by the presence of molasses in the diet and higher content of ADF, which agrees with the results of Azizi-Shotorkhoft et al (2018) who indicated that the inclusion of molasses increased the cellulolytic activities.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…According to a study by Raghuvansi et al (2007) , the increase in the production of fibrolytic enzymes could be attributed to the higher numbers of fibrolytic bacteria. Our results indicated that group S1 showed higher enzymes activities (cellulase and xylanase), and a higher bacterial population followed by S3 ( Table 4 ); this finding could be attributed to the presence of rapidly degradable carbohydrates and degradable nitrogen in S1 groups that stimulated bacterial growth ( Raghuvansi et al, 2007 ; Azizi-Shotorkhoft et al, 2018 ). Moreover, higher cellulase production and bacterial population in S3 compared to S2 could be explained by the presence of molasses in the diet and higher content of ADF, which agrees with the results of Azizi-Shotorkhoft et al (2018) who indicated that the inclusion of molasses increased the cellulolytic activities.…”
Section: Discussionmentioning
confidence: 61%
“…Our results indicated that group S1 showed higher enzymes activities (cellulase and xylanase), and a higher bacterial population followed by S3 ( Table 4 ); this finding could be attributed to the presence of rapidly degradable carbohydrates and degradable nitrogen in S1 groups that stimulated bacterial growth ( Raghuvansi et al, 2007 ; Azizi-Shotorkhoft et al, 2018 ). Moreover, higher cellulase production and bacterial population in S3 compared to S2 could be explained by the presence of molasses in the diet and higher content of ADF, which agrees with the results of Azizi-Shotorkhoft et al (2018) who indicated that the inclusion of molasses increased the cellulolytic activities. On the other hand, Khattab & Tawab (2018) reported that the inclusion of palm fronds in the animal diet reduced microbial protein due to low protein content that depresses microbial growth.…”
Section: Discussionmentioning
confidence: 61%
“…The activities of xylanase and cellulase ( Table 1 ) varied slightly by the inclusion of OC, DD, and DPF in the sheep diet. Higher cellulase and xylanase production could be attributed to the abundance of cellulolytic and xylanolytic bacteria [38] , [39] . On the other hand, Kala et al [40] illustrated that cellulase and xylanase in the buffalo rumen were not affected by diet type.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Raghuvansi et al (2007), the increase in the production of fibrolytic enzymes could be attributed to the higher numbers of fibrolytic bacteria. Our results indicated that group S1 showed higher enzymes activities (cellulase and xylanase), and a higher bacterial population followed by S3 (Table 4); this finding could be attributed to the presence of rapidly degradable carbohydrates and degradable nitrogen in S1 groups that stimulated bacterial growth (Raghuvansi et al, 2007;Azizi-Shotorkhoft et al, 2018). Moreover, higher cellulase production and bacterial population in S3 compared to S2 could be explained by the presence of molasses in the diet and higher content of ADF, which agrees with the results of Azizi-Shotorkhoft et al ( 2018) who indicated that the inclusion of molasses increased the cellulolytic activities.…”
Section: Rumen Fermentation Activitymentioning
confidence: 66%